Cristais fotônicos e luz lenta - Silva Junior, Cícero Julião da (2011)
In this work, an analysis of the characteristics of photonic crystals is carried out. Within the framework of Maxwell’s equations in combination with Bloch’s theorem and Bragg’s resonance condition, one may unveil peculiar phenomena exhibited by these crystals. For one-dimensional photonic crystals, we calculate the photonic band diagram. This diagram is an important tool to design and build crystals of practical value. Then we expand the analysis, generalizing the study to two and three dimensions. Finally, we studied the phenomenon of slow light in photonic crystals and in photonic crystal waveguides, and observe slow light in photonic crystal waveguides via numerical simulations.